Method for connecting brazed sapphire and metal material with assistance of sintered porous titanium

By introducing sintered porous titanium intermediate layer and modified TiZrCuNi active brazing into the brazing connection between sapphire and metal materials, the problems of poor wettability of the brazing material and difficulty in relieving residual stress are solved, and the reliability of the connection is significantly improved.

CN119910260AActive Publication Date: 2025-05-02XIAN THERMAL POWER RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510032592.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-05-02
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The brazed connection between sapphire and metal materials has the problem of poor wetting of the surface of the brazing material on the sapphire and difficult to relieve the residual stress of the joint, resulting in insufficient connection reliability.

Method used

Sintered porous titanium is used as the intermediate layer skeleton structure, and modified TiZrCuNi active brazing material is used to achieve the connection between sapphire and metal material through vacuum brazing.

Benefits of technology

The brazing connection reliability of sapphire and metal materials is improved, residual stress is relieved through the porous titanium intermediate layer, and the surface wetting of sapphire is improved by modifying brazing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910260A_ABST
    Figure CN119910260A_ABST
Patent Text Reader

Abstract

The invention discloses a method for connecting a sintered porous titanium assisted brazing sapphire and a metal material, which comprises the following steps: adding TiZrCuNi brazing filler metal powder into a binder, and uniformly stirring to obtain TiZrCuNi soldering paste, specifically, the TiZrCuNi soldering paste comprises the following raw materials in percentage by mass: 86-91 wt% of TiZrCuNi metal powder and 9-14 wt% of binder; preparing a sintered porous titanium interlayer framework material; the metal base body is arranged on the lower portion, and a TiZrCuNi soldering paste layer with the thickness ranging from 0.2 mm to 0.4 mm is laid on the metal base body; pressing the sintered porous titanium intermediate layer framework material into the solder paste layer, and filling TiZrCuNi metal powder into the sintered porous titanium intermediate layer framework material; tiZrCuNi soldering paste with the thickness of 0.4 mm-0. 6mm is laid on the upper surface of the sintered porous titanium intermediate layer framework material, and sapphire is pressed; and then brazing treatment is conducted, and connection of the sapphire and the metal material is achieved. Residual stress generated by characteristic difference of matrixes on the two sides is relieved, and the brazing connection reliability of the sapphire and the metal is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material connection, and in particular relates to a method for connecting sapphire and metal materials by sintering porous titanium to assist in brazing. Background Art

[0002] Sapphire has good light transmittance and is an ideal material for making infrared optical windows and fairings. It is widely used in optoelectronic equipment inside aircraft, satellites, cruise ships, submarines, etc. In actual engineering applications, sapphire has poor machinability due to its high brittleness and poor toughness. When used, it is often restricted by size and shape. Connecting with metal materials is the first choice for realizing complex structures and large-sized sapphire components.

[0003] Most of the domestic sapphire precision components are connected by adhesive bonding and mechanical connection. The service temperature of adhesive joints should not exceed 300℃, and there is a problem of aging after long-term placement. The brittle material of sapphire has stress concentration at the edge of the processing hole, and the mechanical connection has low bearing capacity. Brazing technology is an important means to achieve ceramic / metal connection, and it is even the only connection method for some key components.

[0004] At present, most sapphire brazing connections use low-melting-point Ag-based and Sn-based solders (patent CN201810393896.2 and paper: Research on the process and mechanism of low-temperature brazing of sapphire with Sn-based solders), and the reliability of sapphire and metal brazing connections needs to be improved. At the same time, sapphire and metal brazing connections mainly face two major problems: poor wettability of the solder on the sapphire surface and difficulty in relieving residual stress in the joint.

[0005] Therefore, improving the reliability of sapphire-metal brazing connections is very necessary to expand the engineering applications of connected components. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for connecting sapphire and metal materials by sintering porous titanium to assist in brazing.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for connecting sapphire and metal materials by sintering porous titanium-assisted brazing, comprising:

[0010] Adding TiZrCuNi solder powder to a binder and stirring evenly to obtain a TiZrCuNi solder paste, wherein the TiZrCuNi metal powder is 86-91wt.%, and the binder is 9-14wt.% based on the mass percentage of the raw materials;

[0011] preparing a sintered porous titanium intermediate layer skeleton material;

[0012] The metal substrate is positioned downward, and a layer of TiZrCuNi solder paste with a thickness of 0.2 mm to 0.4 mm is laid on its upper surface;

[0013] The lower surface of the sintered porous titanium intermediate layer skeleton material is pressed into the solder paste layer on the upper surface of the metal substrate, the surroundings are sealed with TiZrCuNi solder paste, and TiZrCuNi metal powder is filled into the sintered porous titanium intermediate layer skeleton material;

[0014] Lay TiZrCuNi solder paste with a thickness of 0.4 mm to 0.6 mm on the upper surface of the sintered porous titanium intermediate layer skeleton material, and press the sapphire;

[0015] After that, vacuum brazing is performed to connect the sapphire to the metal material.

[0016] As a preferred embodiment of the method of the present invention, the particle size of the TiZrCuNi metal powder is +300 to -100 mesh.

[0017] As a preferred embodiment of the method of the present invention, the binder is composed of a solvent, polyethylene glycol, stearic acid, polyamide wax, oxalic acid and paraffin oil;

[0018] Among them, in terms of mass percent, the solvent is 58-60wt.%, the polyethylene glycol is 12-14wt.%, the stearic acid is 4-6wt.%, the polyamide wax is 5-8wt.%, the oxalic acid is 10-13wt.%, and the paraffin oil is 3-7wt.%.

[0019] As a preferred embodiment of the method of the present invention, the solvent is composed of terpineol and diethylene glycol butyl ether in a volume ratio of 4:3.

[0020] As a preferred embodiment of the method of the present invention, the preparation method of the binder comprises:

[0021] Heat the solvent, polyethylene glycol, stearic acid and polyamide wax in a water bath and stir until they are completely dissolved;

[0022] Then add oxalic acid and paraffin oil, heat and stir until dissolved, to obtain the binder.

[0023] As a preferred embodiment of the method of the present invention, the method for preparing the sintered porous titanium intermediate layer skeleton material comprises:

[0024] Φ1.0mm titanium wire is used as the drawing raw material, and after preheating at 150-180°C, Φ100-150um titanium fiber is prepared by multiple drawing processes;

[0025] The titanium fibers are braided and folded into a multi-layer titanium fiber mesh to obtain a titanium fiber sheet block, wherein the weight of the titanium fibers is calculated by a weighing volume method according to the porosity of the porous titanium, and the porosity of the porous titanium is 50% to 80%;

[0026] A mold is used to pre-press a titanium fiber sheet block, wherein the pre-pressing stress is 80 to 100 MPa and the holding time is 30 to 60 seconds;

[0027] Stress relief annealing heat treatment of the material block;

[0028] A porous titanium block is obtained by pre-pressing a block mold and then pressing, wherein the pressing stress is 150 to 180 MPa and the holding time is 60 to 80 seconds;

[0029] The porous titanium block is sintered to obtain a sintered porous titanium sheet with a specific porosity by controlling the sintering process parameters, wherein the sintering temperature is 1050-1300° C. and the holding time is 120-180 seconds;

[0030] The sintered porous titanium sheet is cut into sheets with the size of length×width×thickness of 10 mm×10 mm×(0.4-1.0 mm) to obtain a sintered porous titanium intermediate layer skeleton material.

[0031] As a preferred embodiment of the method of the present invention, the TiZrCuNi metal powder is filled into the sintered porous titanium intermediate layer skeleton material, wherein the TiZrCuNi metal powder accounts for 8% to 15% of the total mass of the sintered porous titanium intermediate layer skeleton material and the sealed TiZrCuNi solder paste.

[0032] As a preferred embodiment of the method of the present invention, the surface of the metal substrate to be connected is polished, and the polishing method includes:

[0033] Use 400# to 1000# metallographic sandpaper to polish the surface of the metal substrate to be connected, clean and dry the polished surface for later use.

[0034] As a preferred embodiment of the method of the present invention, the upper surface of the sapphire to be brazed is polished to a smooth mirror surface with a surface roughness of 6 to 10 nm.

[0035] As a preferred embodiment of the method of the present invention, the brazing process includes:

[0036] Start by heating to 300-350℃ at 12-18℃ / min, keep warm for 20-30min to ensure that the binder is fully volatilized, then heat to 750-800℃ at 8-11℃ / min, then heat to brazing temperature at 4-7℃ / min, keep warm for 15-35min, and brazing is completed;

[0037] The temperature was lowered to below 300°C at 5-8°C / min, and then cooled in the furnace.

[0038] Beneficial effects of the present invention:

[0039] The present invention discloses a method for connecting sapphire and metal materials by sintered porous titanium-assisted brazing. The method uses a modified TiZrCuNi active brazing filler metal to ensure that the molten brazing filler metal fully wets the sapphire surface. The sintered porous titanium is introduced as an intermediate layer to enable the porous titanium to retain more pore structures, alleviate the residual stress caused by the difference in substrate properties on both sides, and improve the reliability of the brazing connection between the sapphire and the metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0041] Figure 1 It is a schematic diagram of module assembly in an embodiment of the present invention.

[0042] Figure 2 This is a diagram showing the brazing effect in an embodiment of the present invention.

[0043] Figure 3 This is a graph showing the relationship between adding an intermediate layer and the shear strength of the brazed joint in an embodiment of the present invention.

[0044] Figure 4 This is a microstructure diagram of the interface between sapphire and TC4 alloy brazing joint when the binder formula is not properly selected in the embodiment of the present invention. DETAILED DESCRIPTION

[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0046] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0047] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0048] (1) Surface pretreatment of substrate: The upper surface of sapphire to be brazed is polished to a smooth mirror surface with a surface roughness of about 6 to 10 nm;

[0049] Use 400# to 1000# metallographic sandpaper to polish the surface of the metal substrate to be connected, clean and dry the polished surface for later use.

[0050] (2) Brazing system: sapphire / TiZrCuNi brazing material adhesive tape + sintered porous titanium intermediate layer (the thickness of the intermediate layer is about 0.4 mm to 1.0 mm, and the porous skeleton structure is filled with brazing material powder) + TiZrCuNi active brazing material paste / metal matrix.

[0051] A. Preparation of TiZrCuNi active solder paste:

[0052] The TiZrCuNi solder paste is composed of two parts: TiZrCuNi metal powder accounting for about 86-91wt.% and a binder accounting for about 9-14wt.%;

[0053] Select +300~-100 mesh TiZrCuNi spherical powder (prepared by vacuum air atomization method);

[0054] The specific preparation process of TiZrCuNi spherical powder is as follows:

[0055] Ingot melting: vacuum arc melting equipment is used to obtain powdered ingots (composition ratio Ti-37.5Zr-15Cu-10Ni). The furnace is evacuated to 10-2Pa by a three-pole vacuum pump. After the furnace is filled with argon to wash 3-4 times, it is evacuated to 10-2Pa and filled with argon to 0.06MPa again. Before the formal smelting, a piece of industrial pure titanium is repeatedly smelted to further remove residual oxygen in the atmosphere. In order to make the composition of the solidified alloy uniform, the sample in the water-cooled copper crucible is repeatedly melted 5 to 6 times under electromagnetic stirring.

[0056] EIGA process for preparing powder: the prefabricated alloy rod is regionally refined under 10-3Pa vacuum conditions, the metal liquid continuously flows vertically through the nozzle, and the metal liquid is atomized and broken into a large number of fine droplets by the high-pressure airflow through the tightly coupled nozzle, and the fine droplets solidify into particles in flight;

[0057] The process parameters adopted are an annular gap nozzle, an atomization pressure of 5 to 7 MPa and a smelting power of 20 to 30 kW.

[0058] The binder formula ranges from 58 to 60 wt.% solvent (pinene alcohol: diethylene glycol butyl ether = 4:3), 12 to 14 wt.% polyethylene glycol, 4 to 6 wt.% stearic acid, 5 to 8 wt.% polyamide wax, 10 to 13 wt.% oxalic acid, and 3 to 7 wt.% paraffin oil;

[0059] The powder is ball-milled in the vacuum mixer for 1 to 2 hours at a speed of 200 to 400 r / min to ensure uniform distribution of solder powder. The entire solder paste preparation process is completed in a glove box with an oxygen content of <20ppm.

[0060] Adhesive preparation process: water bath heating (temperature about 80-90°C), mechanical stirring to completely dissolve the thickener, then mix other additives in proportion (terpineol and diethylene glycol butyl ether as solvents, polyethylene glycol, stearic acid, polyamide wax as thickeners, oxalic acid, paraffin oil as other additives), heat and stir until various chemical reagents are dissolved, and complete the preparation of the adhesive;

[0061] Add TiZrCuNi solder powder to the binder according to the principle of "small amounts and multiple times" (the first addition amount of TiZrCuNi solder powder is ≤80g, and the amount of powder added each time thereafter is <5g, and 4 to 5 additions are completed in succession and fully stirred, the total amount of powder added is ≥100g, and at least 5 additions are performed), and after stirring evenly, the solder paste is put into a special solder bottle and sealed for storage for later use.

[0062] B. Preparation of sintered porous titanium intermediate layer skeleton structure:

[0063] The sintered porous titanium intermediate layer skeleton structure is prepared by using commercially available annealed Φ1.0 mm titanium wire as the drawing raw material, and after preheating at 150-180°C, titanium fibers with a diameter of Φ100-150 μm are prepared by multiple wire drawing.

[0064] Titanium fiber specific preparation process:

[0065] Before each drawing, the titanium wire is cleaned with a mixture of sulfuric acid, nitric acid and water (volume ratio 1:2:4) for 5 to 7 minutes, paraffin oil is used as a drawing lubricant, and annealing is carried out in a sodium hydroxide melt. The surface reduction rate of the process from Φ1.0mm to Φ0.4mm is controlled at 25% to 30%, and the surface reduction rate of the process from Φ0.4mm to Φ0.1 to Φ0.15mm is controlled at 8% to 10%.

[0066] Preparation process of the intermediate layer titanium fiber skeleton structure:

[0067] Titanium fiber weaving and folding to form a multi-layer titanium fiber mesh → Calculate the required titanium fiber mesh weight by direct weighing volume method according to the designed porous titanium porosity (50% to 80%) → Pre-press titanium fiber sheet block with sheet mold (pre-pressing stress is 80 to 100 MPa, holding time is 30 to 60 seconds) → Stress relief annealing heat treatment of the block (annealing temperature selection principle: 120 to 150 ° C at the a / β phase transition point of titanium alloy, air cooling; the phase transition point temperature of pure titanium or titanium fiber is 882.5 ° C, and the annealing heat treatment process is: annealing temperature 732.5 to 762. 5℃, air cooling) → pre-press the material block mold and then press (the re-pressing stress is 150-180MPa, and the holding time is 60-80s) → prepare sintered porous titanium under different sintering processes (holding time 120-180s and sintering temperature 1050-1300℃) → conduct porosity and thermal expansion coefficient measurement and verification → optimize sintering process parameters → prepare sintered porous titanium sheets with specific porosity as the middle layer → cut the sintered porous titanium sheets to obtain the middle layer titanium fiber skeleton structure with a size of 10mm×10mm×(0.3-0.5mm).

[0068] C. Assembly of modules of the intermediate layer system: The metal substrate test block is positioned at the bottom, and a layer of TiZrCuNi solder paste with a thickness of 0.1mm to 0.5mm is laid on it. The sintered porous titanium intermediate layer skeleton structure is pressed into the solder paste layer (thin layer bottom sealing). An appropriate amount of +300 to -100 mesh TiZrCuNi spherical powder is determined to be filled into the sintered porous titanium intermediate layer skeleton structure (the porous skeleton structure is filled with solder powder). A TiZrCuNi solder adhesive tape with a thickness of 0.4mm to 0.6mm is laid on the upper surface of the sintered porous titanium intermediate layer skeleton structure, and the sapphire is pressed tightly.

[0069] (4) Brazing process: Start by heating the temperature to 300-350°C at 12-18°C / min, keep it at that temperature for 20-30min to ensure that the binder is fully volatilized, then heat it to 750-800°C at 8-11°C / min, then heat it to the brazing temperature at 4-7°C / min, keep it at that temperature for 15-35min, and when brazing is complete, cool it to below 300°C at 5-8°C / min, and then cool it with the furnace.

[0070] Example 1

[0071] See the module assembly diagram in this embodiment. Figure 1 , the specific instructions are as follows:

[0072] (1) Surface pretreatment of substrate: The upper surface of sapphire to be brazed is polished to a smooth mirror surface with a surface roughness of about 6 to 10 nm;

[0073] Use 400# to 1000# metallographic sandpaper to polish the surface of the metal substrate to be connected, clean and dry the polished surface for later use.

[0074] (2) Preparation of TiZrCuNi active solder paste:

[0075] The TiZrCuNi solder paste consists of two parts: about 86wt.% TiZrCuNi metal powder and about 14wt.% binder;

[0076] TiZrCuNi metal powder is selected from +300 to -100 mesh powder;

[0077] Binder formula: 58wt.% solvent (pinene alcohol: diethylene glycol butyl ether = 4:3, V / V), 13wt.% polyethylene glycol, 6wt.% stearic acid, 7wt.% polyamide wax, 12wt.% oxalic acid, 4wt.% paraffin oil;

[0078] Adhesive preparation process: water bath heating (temperature about 80-90℃), mechanical stirring to make the thickener completely dissolved, then mix other additives in proportion, heat and stir until all kinds of chemical reagents are dissolved, and complete the preparation of adhesive;

[0079] Add TiZrCuNi solder powder into the binder according to the principle of "small amounts and multiple times". After stirring evenly, put the solder paste into a special solder bottle and seal it for storage.

[0080] (3) Preparation of sintered porous titanium intermediate layer skeleton structure:

[0081] Titanium fibers are woven and folded to form a multi-layer titanium fiber mesh → the required titanium fiber mesh weight is calculated by direct weighing volume method according to the designed porous titanium porosity (50% to 80%) → the titanium fiber sheet block is pre-pressed using a sheet mold (pre-pressing stress is 80 to 100 MPa, and the holding time is 30 to 60 s) → the block is subjected to stress relief annealing heat treatment → the pre-pressed block mold is re-pressed (the re-pressing stress is 150 to 180 MPa, and the holding time is 60 to 80 s) → sintered porous titanium is prepared under different sintering process conditions (holding time 130 s and sintering temperature 1100°C) → porosity and thermal expansion coefficient are measured and verified → sintering process parameters are optimized → a sintered porous titanium sheet with a specific porosity is prepared as an intermediate layer → the sintered porous titanium sheet is cut to obtain an intermediate layer titanium fiber skeleton structure with a size of 10 mm × 10 mm × (0.4 mm) (the porosity of the intermediate layer skeleton structure is 58.5%).

[0082] (4) Assembly of each module

[0083] The metal substrate test block is positioned at the bottom, and a layer of TiZrCuNi solder paste with a thickness of 0.2 mm is laid on it. The sintered porous titanium intermediate layer (thickness of 0.4 mm) skeleton structure is pressed into the solder paste layer (thin layer bottom seal), and an appropriate amount (accounting for the intermediate layer system: the surrounding and bottom solder paste + porous titanium intermediate layer skeleton mass percentage is 8%) + 300~-100 mesh TiZrCuNi spherical powder is filled into the sintered porous titanium intermediate layer skeleton structure, and a TiZrCuNi solder adhesive tape with a thickness of 0.4 mm is laid on the upper surface of the sintered porous titanium intermediate layer skeleton structure, and the sapphire is pressed tightly.

[0084] (5) Brazing process:

[0085] Start by heating to 330℃ at 16℃ / min, keep warm for 25min to ensure that the binder is fully volatilized, then heat to 780℃ at 10℃ / min, then heat to brazing temperature at 6℃ / min, keep warm for 20min, brazing is complete, cool to below 300℃ at 8℃ / min, and then cool with the furnace. Figure 2 .

[0086] (6) Performance test:

[0087] The relationship between adding an intermediate layer and the shear strength of the brazed joint is shown in Figure 3 .

[0088] The shear test of brazed joints was completed in accordance with the relevant requirements of GB / T 11363-2008. The moving speed of the pressure head was 0.5 mm / s, and the shear strength of the joint was taken as the average of three valid test values.

[0089] in, Figure 3The process of direct brazing with medium solder is as follows: start heating to 330℃ at 16℃ / min, keep warm for 25min to ensure that the binder is fully volatilized, then heat to 780℃ at 10℃ / min, then heat to 930℃ at 6℃ / min, keep warm for 20min, brazing is completed, cool to below 300℃ at 8℃ / min, and then cool with the furnace.

[0090] It can be seen that under the same brazing process conditions (930℃ / 20min), a 0.4mm thick sintered porous titanium intermediate layer and brazing material were introduced to directly braze sapphire and TC4 alloy. The shear strengths of the joints were 26.85MPa and 15.62MPa respectively. The shear strength of the former was 11.23MPa higher than that of the latter.

[0091] Example 2

[0092] (1) Surface pretreatment of substrate: The upper surface of sapphire to be brazed is polished to a smooth mirror surface with a surface roughness of about 6 to 10 nm;

[0093] Use 400# to 1000# metallographic sandpaper to polish the surface of the metal substrate to be connected, clean and dry the polished surface for later use.

[0094] (2) Preparation of TiZrCuNi active solder paste:

[0095] The TiZrCuNi solder paste consists of two parts: about 86wt.% TiZrCuNi metal powder and about 14wt.% binder;

[0096] TiZrCuNi metal powder is selected from +300 to -100 mesh powder;

[0097] Binder formula: 58wt.% solvent (pinene alcohol: diethylene glycol butyl ether = 4:3), 13wt.% polyethylene glycol, 6wt.% stearic acid, 7wt.% polyamide wax, 12wt.% oxalic acid, 4wt.% paraffin oil;

[0098] Adhesive preparation process: water bath heating (temperature about 80-90℃), mechanical stirring to make the thickener completely dissolved, then mix other additives in proportion, heat and stir until all kinds of chemical reagents are dissolved, and complete the preparation of adhesive;

[0099] Add TiZrCuNi solder powder into the binder according to the principle of "small amounts and multiple times". After stirring evenly, put the solder paste into a special solder bottle and seal it for storage.

[0100] (3) Preparation of sintered porous titanium intermediate layer skeleton structure:

[0101] Titanium fibers are woven and folded to form a multi-layer titanium fiber mesh → the required titanium fiber mesh weight is calculated by direct weighing volume method according to the designed porous titanium porosity (50% to 80%) → the titanium fiber sheet block is pre-pressed using a sheet mold (pre-pressing stress is 80 to 100 MPa, and the holding time is 30 to 60 s) → the block is subjected to stress relief annealing heat treatment → the pre-pressed block mold is re-pressed (the re-pressing stress is 150 to 180 MPa, and the holding time is 60 to 80 s) → sintered porous titanium is prepared under different sintering process conditions (holding time 150 s and sintering temperature 1200°C) → porosity and thermal expansion coefficient are measured and verified → sintering process parameters are optimized → a sintered porous titanium sheet with a specific porosity is prepared as an intermediate layer → the sintered porous titanium sheet is cut to obtain an intermediate layer titanium fiber skeleton structure with a size of 10 mm × 10 mm × (0.8 mm) (porosity is 79.3%).

[0102] (4) Assembly of each module

[0103] The metal substrate test block is positioned at the bottom, and a layer of TiZrCuNi solder paste with a thickness of 0.2 mm is laid on it. The sintered porous titanium intermediate layer (thickness of 0.4 mm) skeleton structure is pressed into the solder paste layer (thin layer bottom seal), and an appropriate amount (accounting for the intermediate layer system: the surrounding and bottom solder paste + porous titanium intermediate layer skeleton mass percentage is 8%) + 300~-100 mesh TiZrCuNi spherical powder is filled into the sintered porous titanium intermediate layer skeleton structure, and a TiZrCuNi solder adhesive tape with a thickness of 0.8 mm is laid on the upper surface of the sintered porous titanium intermediate layer skeleton structure, and the sapphire is pressed tightly.

[0104] (5) Brazing process:

[0105] Start by raising the temperature to 330°C at 16°C / min, keeping it warm for 25 minutes to ensure that the binder is fully volatilized, then raise it to 780°C at 10°C / min, and then raise it to the brazing temperature at 6°C / min, keep it warm for 20 minutes. When brazing is completed, cool it down to below 300°C at 8°C / min, and then cool it with the furnace.

[0106] (6) Performance test:

[0107] The relationship between adding an intermediate layer and the shear strength of the brazed joint is shown in Figure 3 . The shear test of brazed joints was completed in accordance with the relevant requirements of GB / T 11363-2008. The moving speed of the indenter was 0.5 mm / s, and the shear strength of the joint was the average of three valid test values. Under the same brazing process (930°C / 20min), a 0.8 mm thick sintered porous titanium intermediate layer and brazing material were introduced to directly braze sapphire and TC4 alloy. The shear strength of the joints was 31.81 MPa and 15.62 MPa, respectively. The former was 16.19 MPa higher than the latter.

[0108] Example 3

[0109] (1) Surface pretreatment of the substrate: Use 400# to 1000# metallographic sandpaper to polish the sapphire to be brazed and the metal substrate to be connected, and then clean and dry the polished surface for later use.

[0110] (2) Preparation of TiZrCuNi active solder paste:

[0111] The TiZrCuNi solder paste consists of two parts: about 86wt.% TiZrCuNi metal powder and about 14wt.% binder;

[0112] TiZrCuNi metal powder is selected from +300 to -100 mesh powder;

[0113] Binder formula: 58wt.% solvent (pinene alcohol: diethylene glycol butyl ether = 4:3), 13wt.% polyethylene glycol, 6wt.% stearic acid, 7wt.% polyamide wax, 12wt.% oxalic acid, 4wt.% paraffin oil;

[0114] Adhesive preparation process: water bath heating (temperature about 80-90℃), mechanical stirring to make the thickener completely dissolved, then mix other additives in proportion, heat and stir until all kinds of chemical reagents are dissolved, and complete the preparation of adhesive;

[0115] Add TiZrCuNi solder powder into the binder according to the principle of "small amounts and multiple times". After stirring evenly, put the solder paste into a special solder bottle and seal it for storage.

[0116] (3) Preparation of sintered porous titanium intermediate layer skeleton structure:

[0117] Titanium fibers are woven and folded to form a multi-layer titanium fiber mesh → the required titanium fiber mesh weight is calculated by direct weighing volume method according to the designed porous titanium porosity (50% to 80%) → the titanium fiber sheet block is pre-pressed using a sheet mold (pre-pressing stress is 80 to 100 MPa, and holding time is 30 to 60 s) → the block is subjected to stress relief annealing heat treatment → the pre-pressed block mold is re-pressed (re-pressing stress is 150 to 180 MPa, and holding time is 60 to 80 s) → sintered porous titanium is prepared under different sintering processes (holding time 180 s and sintering temperature 1250°C) → porosity and thermal expansion coefficient are measured and verified → sintering process parameters are optimized → sintered porous titanium sheets with specific porosity are prepared as intermediate layers → the sintered porous titanium sheets are cut to obtain an intermediate layer titanium fiber skeleton structure with a size of 10 mm × 10 mm × (1.0 mm) (porosity is 67.6%).

[0118] (4) Assembly of each module

[0119] The metal substrate test block is positioned at the bottom, and a layer of TiZrCuNi solder paste with a thickness of 0.2 mm is laid on it. The sintered porous titanium intermediate layer (thickness of 0.4 mm) skeleton structure is pressed into the solder paste layer (thin layer bottom seal), and an appropriate amount (accounting for the intermediate layer system: the surrounding and bottom solder paste + porous titanium intermediate layer skeleton mass percentage is 8%) + 300~-100 mesh TiZrCuNi spherical powder is determined to be filled into the sintered porous titanium intermediate layer skeleton structure, and a TiZrCuNi solder adhesive tape with a thickness of 1.0 mm is laid on the upper surface of the sintered porous titanium intermediate layer skeleton structure, and the sapphire is pressed tightly.

[0120] (5) Brazing process:

[0121] Start by raising the temperature to 330°C at 16°C / min, keeping it warm for 25 minutes to ensure that the binder is fully volatilized, then raise it to 780°C at 10°C / min, and then raise it to the brazing temperature at 6°C / min, keep it warm for 20 minutes. When brazing is completed, cool it down to below 300°C at 8°C / min, and then cool it with the furnace.

[0122] (6) Performance test:

[0123] The relationship between adding an intermediate layer and the shear strength of the brazed joint is shown in Figure 3 The shear test of brazed joints was completed in accordance with the relevant requirements of GB / T 11363-2008. The moving speed of the pressure head was 0.5 mm / s, and the shear strength of the joint was the average of three valid test values.

[0124] Under the same brazing process conditions (930℃ / 20min), a 1.0mm thick sintered porous titanium intermediate layer and brazing filler metal were introduced to directly braze sapphire and TC4 alloy. The shear strengths of the joints were 27.66MPa and 15.62MPa, respectively. The shear strength of the former was 12.04MPa higher than that of the latter.

[0125] Comparative Example 1

[0126] Under the conditions of Example 1, the binder formulation is different, and the other conditions are the same as those of Example 1 for brazing treatment;

[0127] The binder formula is: 56wt.% solvent (pinene alcohol: diethylene glycol butyl ether = 4:3, V / V), 13wt.% polyethylene glycol, 6wt.% stearic acid, 9wt.% polyamide wax, 12wt.% oxalic acid, and 4wt.% paraffin oil.

[0128] See the microstructure diagram of the interface between sapphire and TC4 alloy brazed joint for details. Figure 4 It can be seen that there is an obvious high-carbon residual phase in the brazing seam, which significantly reduces the brazing quality of sapphire and metal.

[0129] At the same time, the percentage content of polyethylene glycol or stearic acid is higher than the required range of the present invention or the binder preparation method is improper, resulting in the presence of obvious high-carbon residual phase in the brazing seam.

[0130] The present invention directly adopts TiZrCuNi active solder with higher activity and better high-temperature service performance of the brazed joint for brazing; adopts sintered porous titanium as the intermediate layer skeleton structure to retain more pores for alleviating the residual stress caused by the difference in substrate properties on both sides of the sapphire / metal substrate; under the same solder and the same brazing process conditions, compared with the shear strength of the direct brazed joint, the shear strength of the sapphire and TC4 alloy joints brazed with the addition of 0.4, 0.8 and 1.0 mm sintered porous titanium intermediate layers is increased by 11.23, 16.19 and 12.04 MPa respectively.

[0131] A layer of TiZrCuNi solder paste with a thickness of 0.2 mm to 0.4 mm is laid on the metal substrate test block of the present invention, the sintered porous titanium intermediate layer skeleton structure is pressed into the solder paste layer (thin layer bottom sealing), and a TiZrCuNi solder adhesive tape with a thickness of 0.4 mm to 0.6 mm is laid on the upper surface of the sintered porous titanium intermediate layer skeleton structure to press the sapphire; the solder thickness on the metal substrate side is significantly thinner than that on the sapphire side, which promotes the formation of an interface with the sapphire side and inhibits the metal side interface corrosion.

[0132] The present invention uses sintered porous titanium as an intermediate layer, the pores provide channels for molten solder to flow to sapphire, the fiber skeleton supplements the Ti source for the solder, and the multi-point interface reaction promotes the solder wetting the sapphire and accelerates the formation of a continuous interface reaction layer.

[0133] A proper amount of powdered solder is also filled into the fiber skeleton of the present invention to provide sufficient Ti source for the interface reaction between the solder and sapphire.

[0134] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for connecting sapphire and metal materials by sintering porous titanium assisted brazing, characterized in that: include, Adding TiZrCuNi solder powder to a binder and stirring evenly to obtain a TiZrCuNi solder paste, wherein the TiZrCuNi metal powder is 86-91wt.%, and the binder is 9-14wt.% based on the mass percentage of the raw materials; preparing a sintered porous titanium intermediate layer skeleton material; The metal substrate is positioned downward, and a layer of TiZrCuNi solder paste with a thickness of 0.2 mm to 0.4 mm is laid on its upper surface; The lower surface of the sintered porous titanium intermediate layer skeleton material is pressed into the solder paste layer on the upper surface of the metal substrate, the surroundings are sealed with TiZrCuNi solder paste, and TiZrCuNi metal powder is filled into the sintered porous titanium intermediate layer skeleton material; Lay TiZrCuNi solder paste with a thickness of 0.4 mm to 0.6 mm on the upper surface of the sintered porous titanium intermediate layer skeleton material, and press the sapphire; After that, vacuum brazing is performed to connect the sapphire to the metal material.

2. The method according to claim 1, characterized in that: The particle size of the TiZrCuNi metal powder is +300 to -100 mesh.

3. The method according to claim 1 or 2, characterized in that: The binder is composed of a solvent, polyethylene glycol, stearic acid, polyamide wax, oxalic acid and paraffin oil; Among them, in terms of mass percent, the solvent is 58-60wt.%, the polyethylene glycol is 12-14wt.%, the stearic acid is 4-6wt.%, the polyamide wax is 5-8wt.%, the oxalic acid is 10-13wt.%, and the paraffin oil is 3-7wt.%.

4. The method according to claim 3, characterized in that: The solvent is composed of terpineol and diethylene glycol butyl ether in a volume ratio of 4:

3.

5. The method according to claim 3, characterized in that: The preparation method of the binder comprises: Heat the solvent, polyethylene glycol, stearic acid and polyamide wax in a water bath and stir until they are completely dissolved; Then add oxalic acid and paraffin oil, heat and stir until dissolved, to obtain the binder.

6. The method according to claim 1, characterized in that: The method for preparing the sintered porous titanium intermediate layer skeleton material comprises: Φ1.0mm titanium wire is used as the drawing raw material, and after preheating at 150-180°C, Φ100-150um titanium fiber is prepared by multiple drawing processes; The titanium fibers are braided and folded into a multi-layer titanium fiber mesh to obtain a titanium fiber sheet block, wherein the weight of the titanium fibers is calculated by a weighing volume method according to the porosity of the porous titanium, and the porosity of the porous titanium is 50% to 80%; A mold is used to pre-press a titanium fiber sheet block, wherein the pre-pressing stress is 80 to 100 MPa and the holding time is 30 to 60 seconds; Stress relief annealing heat treatment of the material block; A porous titanium block is obtained by pre-pressing a block mold and then pressing, wherein the pressing stress is 150 to 180 MPa and the holding time is 60 to 80 seconds; The porous titanium block is sintered to obtain a sintered porous titanium sheet with a specific porosity by controlling the sintering process parameters, wherein the sintering temperature is 1050-1300° C. and the holding time is 120-180 seconds; The sintered porous titanium sheet is cut into sheets with the size of length×width×thickness of 10 mm×10 mm×(0.4-1.0 mm) to obtain a sintered porous titanium intermediate layer skeleton material.

7. The method according to claim 1, characterized in that: The TiZrCuNi metal powder is filled into the sintered porous titanium intermediate layer skeleton material, wherein the TiZrCuNi metal powder accounts for 8% to 15% of the total mass of the sintered porous titanium intermediate layer skeleton material and the blocked TiZrCuNi solder paste.

8. The method according to claim 1, characterized in that: The surface to be connected of the metal substrate is polished, and the processing method includes: Use 400# to 1000# metallographic sandpaper to polish the surface of the metal substrate to be connected, clean and dry the polished surface for later use.

9. The method according to claim 1 or 8, characterized in that: The upper surface of the sapphire to be brazed is a smooth and flat mirror surface after polishing, and the surface roughness is 6-10nm.

10. The method according to any one of claims 1, 2, 4 to 8, characterized in that: The brazing process comprises: Start by heating to 300-350℃ at 12-18℃ / min, keep warm for 20-30min to ensure that the binder is fully volatilized, then heat to 750-800℃ at 8-11℃ / min, then heat to brazing temperature at 4-7℃ / min, keep warm for 15-35min, and brazing is completed; The temperature was lowered to below 300°C at 5-8°C / min, and then cooled in the furnace.

Citation Information

Patent Citations

  • Ag-CuO-B2O3 brazing filler metal, preparation method thereof and method for connecting sapphire by utilizing Ag-CuO-B2O3 brazing filler metal

    CN110405379A

  • Solder, preparation method thereof and method for connecting sapphire and niobium or niobium alloys by using solder

    CN103056553A

  • Preparation and soldering methods for Ni-based solder used for soldering Nb-Ti high-temperature alloy

    CN107160059A

  • Single crystal alumina low-temperature brazing method

    CN108907385A

  • Method for in-situ generation of Ti7Al5Si12 reinforced brazing seam from foamed titanium

    CN114799394A